Epidemiology of Revision Total Knee Arthroplasty: A Single Center's Experience - Kulshrestha, Vikas (Indian J Orthop, 2019)
BACKGROUND: There has been a gradual increase in the revision TKA (RTKA) workload due to expanding indications of total knee arthroplasty (TKA), coupled with improving patient longevity. Western countries are already looking at their data on RTKA to plan for the future heath care needs of these patients. Limited data is available on RTKA from developing countries. Our study attempts to fill this gap in knowledge. MATERIALS AND METHODS: We prospectively documented details of all RTKA performed at our centre for a period of six years (2011-16). We recorded the volume, causes and time to failure from index surgery of all RTKA and further recorded microbiological pattern in septic failures. We looked at the proportion of each cause of failure and time from index surgery. RESULTS: Of the 5068 TKA procedures performed from January 2011 to December 2016, 201 (4%) were first-time revisions. The predominant cause of revisions was prosthetic infection (61%) followed by aseptic loosening (18%) and instability (7%). In the early, mid term, and late-failure groups, prosthetic infection remained the main cause of failure. In 47% of the septic revisions, the offending organisms could be identified and of those identified most (67%) were Gram-negative. CONCLUSION: The volume of first-time RTKA procedures (4%) at our center remained low compared with that of the Western countries. In Western countries, the incidence of late aseptic failures was higher than that of early-septic failures, whereas in our study, revisions were more commonly performed in the early-failure group (48%) and most failures were due to prosthetic infection (61%).